Analisis Perwatakan Tokoh Utama pada Novel Hujan Karya Tere Liye: Kajian Psikologi Sastra - Nur Asikin; Septi Gumiandri (Universitas Muhammadiyah Enrekang, 2023)
This study aims to describe and identify the character of the main character in the novel entitled